1982
DOI: 10.1002/hlca.19820650402
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Nitroaldol Derivatives

Abstract: SummaryThree methods are described by which diastereomerically enriched nitroaldols and their O-silylated derivatives can be prepared. threo-Nitroaldols prevail up to 10: 1 over the erythro-isomers if doubly deprotonated nitroaldols 28 are quenched with acetic acid (THF/HMPT or DMPU, -looo) (see Scheme 5 and Table 2). O-Trimethyl-or O-(f-butyl)dimethylsilylated (TBDMSi) erythro-nitroaldols can be obtained by protonation of the corresponding lithium nitronates (35, 39) in THF at low temperature (see Schemes 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(142 citation statements)
references
References 74 publications
5
131
0
6
Order By: Relevance
“…However, the enantiomer ratio could Helvetica Chimica Acta ± Vol. 82 (1999) 2368 4 ) We have reported on stereoselective protonations of nitronates formed during Henry reactions or by deprotonation of 1,2-dinitro-alcohol derivatives many years ago [9]. These reactions are highly diastereoselective at low temperatures.…”
Section: (Entry 7)mentioning
confidence: 96%
“…However, the enantiomer ratio could Helvetica Chimica Acta ± Vol. 82 (1999) 2368 4 ) We have reported on stereoselective protonations of nitronates formed during Henry reactions or by deprotonation of 1,2-dinitro-alcohol derivatives many years ago [9]. These reactions are highly diastereoselective at low temperatures.…”
Section: (Entry 7)mentioning
confidence: 96%
“…Noteworthy developments to the Henry reaction have been achieved by using silyl nitronates in the existence of fluoride ion or instead α-α doubly deprotonated primary nitroalkanes [9]. Both of these processes have showed to be valuable for the stereo selective preparation of vicinal amino alcohols under drastic conditions, which reduced diastereoselectivity with aromatic aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on hydrogenations with other reagents such as lithium borohydride or lithium aluminum hydride are not consistent in terms of preservation of the configuration. [15][16][17] Therefore a few attempts of these reactions were performed in order to determine their applicability to our case. We found that during hydrogenation using Raney nickel as catalyst, for larger scale experiments the threo-nitro derivative epimerized under formation of the two amino diastereoisomers, as shown by NMR spectra of the reaction mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…This classic method is performed under diverse catalytic conditions and has been frequently reviewed. 15,16 The synthesis of 2-nitrooctadecane-1,3-diol starting from 2 and 3 has been described earlier, for both diasteromers and their mixtures. [8][9][10] The mixture of nitrodiol diastereomers (4 + 5 and 7 + 9) was recrystallized from various solvents to give one single isomer.…”
mentioning
confidence: 99%